Rhabdomyosarcoma of the Breast in Adolescent and Young Adult (AYA) Women. Issue 1 (January 2017) - Audino, Anthony N.; Setty, Bhuvana A.; Yeager, Nicholas D.
Abstract : Soft tissue sarcoma constitutes 8% of all tumors in adolescent and young adults (AYA), with rhabdomyosarcoma (RMS) accounting for 5.2% to 6.5% of the soft tissue sarcoma total within this group. AYAs have a higher propensity for metastasis and inferior outcomes. Metastases to the breast have been reported in ∼3% to 6% of RMS cases. A review of our hospital's tumor registry identified cases of RMS diagnosed between January 1, 2004 and December 31, 2013. A total of 46 patients with RMS were identified, having a mean age of 12.5 years (range, 1 to 49 y). There were 26 males (57%) and 20 females (43%). Eighteen patients (39%) were AYAs, including 10 women. Four patients (8.7%) were identified with breast involvement, all of whom were AYA females. Treatment modalities included chemotherapy, surgical resection, and radiation. One patient is a long-term survivor. Although RMS is uncommon in AYAs, breast involvement occurs almost exclusively in AYA women and is associated with alveolar histology, metastatic disease, and poor outcomes. In total, 4/10 of all AYA females had breast involvement. Routine examination or imaging of the breasts in AYAs with RMS is not currently standard practice at diagnosis or follow-up, but this analysis suggests it should be considered in female AYA patients.